A real-time test-bed for the differential space-time block code modulation for wideband CDMA - Umali, Edwin M. (2003)
The differential space-time block code modulation for Direct Sequence Code Division Multiple Access (DSTBC-CDMA) system combines the merits of differential detection based on space-time block codes and spread spectrum technology for the improvement of the performance of the CDMA system in a fast time-dispersive channel [16]. Simulation results indicate that, indeed, there are benefits in using this new scheme. However, the practical implementation of the new wireless communication scheme was never studied. The required computing power to attain the necessary output data rate and the effect of using a different data representation were never included in the results. In this research, the new wireless communication scheme is adapted to a wideband CDMA system operating at a chip rate of 3.84 Mchips/sec and an output data rate of 240kbits/sec. Simulation results indicate a 13-dB loss in performance when compared to DSTBC-CDMA system. This loss can be attibuted to the high autocorrelation values of the spreading codes. The differential space-time block code deterministic de-prefix (D-Det-DP) downlink receiver [16] is implemented real-time on a TMSS320C6201 evaluation module to study the design issues involved in implementing the new system. The new test-bed cam measure the performance of the new system using a software/hardware simulation environment. The results using the test-bed validate the results of the simulation.